CONCEPTUALIZING FRIENDSHIP THROUGH AMERICAN GAY TELEVISION SERIES IN 2000S - Rudy Rudy (Rubikon : Journal of Transnational American Studies, 2015)
Gay culture has been one of the most phenomenal issues in the world, particularly in the United States. As this culture has become pro and contra over American regarding their point of view, ethically or unethically, thus, it has been spread all over the world through media, particularly television, which makes it unique and essential to observe through the television series, gay characters appear with certain features attached to them. This study concentrates on the depiction of gay shown through American gay television series in 2000s. As gay culture is strongly connected to the collectivity, the friendship among minority groups like gay people has become fascinating to identify. By focusing on how and why the friendship is portrayed through the gay television series, this study incorporates semiotic approach to identify the friendship among gay shown by the American gay television series in 2000s. The observation of the gay television series have revealed that friendship among gay people plays a significant role in gay culture. The research findings show that the depiction of friendship through the gay TV series symbolizes similar values and vision shared among gay people in order to reach solidarity. Additionally, strong friendship as a binding value is always the feature shown by oppressed minority groups in a society.Keywords: Gay, Television Series, 2000s, Friendship, America Culture